Linking college mission statements to cost containment strategies. Issue 4 (7th May 2019) - Simon, Jessica K.; Way, Megan McDonald; Polutnik, Lidija; Albright, Jeremy
Abstract : Purpose: Leaders at higher education institutions (HEIs) in the USA experience substantial pressure to contain costs while advancing their educational missions. The purpose of this paper is to explore the association between publicly stated academic cost-containment objectives found in HEI's strategic plans and mission statements, which help to unify stakeholders and link strategy to an organization's purpose. Design/methodology/approach: This paper analyzes mission statements and strategic plans of 57 small, private HEIs in the Northeastern USA. HEIs in this sample published strategic plans with an explicit cost-containment goal. Mission statements were analyzed for readability. Thematic analysis was conducted using the balanced scorecard approach. Associations between a stated academic cost containment goal and mission statement themes are presented using logistic regression. Findings: Mission statements of HEIs focused on academic cost containment are wordier and more varied. They tend not to mention "liberal arts, " a potential signal of a high-quality, high-cost school; less selective schools may be more likely to emphasize academic cost cutting. Research limitations/implications: This paper contributes to the literature demonstrating mission statements' role in goal setting. Further, it considers college costs from college administrators' perspectives. Given the small sample size, future work should expand the sample and use case studies to explore how mission shapes or constrains strategic objectives. Originality/value: This is the first paper using qualitative and quantitative analysis to explore the association between the mission statements of small HEIs and academic cost containment goals in strategic plans, documents intended to support differentiation in a crowded market.